The Speech Acts in the Surah Al-Fatihah: A Pragmatic Study - Nurfithri Nurfithri (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
This study will examinethe Translation of Surah Al-Fatihah from the perspective ofPragmatic. This study basically focuses on the types of speech act and what does it function related to the tafseer. The method that used in this research is a qualitative method.This analysis is based on Levinson (1983) which focuses on the types of speech act. The findings indicate that there are three kinds of speech act in the Surah Al-Fatihah, they are representative, expressive, and directive.